2011
DOI: 10.1158/0008-5472.can-10-1872
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab Has Preferential Activity against Breast Cancers Driven by HER2 Homodimers

Abstract: In breast cancer cells with HER2 gene amplification, HER2 receptors exist on the cell surface as monomers, homodimers and heterodimers with EGFR/HER3. The therapeutic antibody trastuzumab, an approved therapy for HER2+ breast cancer, cannot block ligand-induced HER2 heterodimers, suggesting it cannot effectively inhibit HER2 signaling. Hence, HER2 oligomeric states may predict the odds of a clinical response to trastuzumab in HER2-driven tumors. To test this hypothesis, we generated non-transformed human MCF10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
144
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(163 citation statements)
references
References 49 publications
12
144
1
1
Order By: Relevance
“…21). In contrast with the antibody trastuzumab that recognizes an epitope on the extracellular domain that is only exposed in the case of HER2 homodimers (21,22), the TKI lapatinib inhibits the intracellular domains of EGFR and HER2, and as such may also target various HER2-containing heterodimers. HER3 has a docking site for the p85 subunit of PI3K and acts as the preferred heterodimerization partner for HER2.…”
Section: Discussionmentioning
confidence: 99%
“…21). In contrast with the antibody trastuzumab that recognizes an epitope on the extracellular domain that is only exposed in the case of HER2 homodimers (21,22), the TKI lapatinib inhibits the intracellular domains of EGFR and HER2, and as such may also target various HER2-containing heterodimers. HER3 has a docking site for the p85 subunit of PI3K and acts as the preferred heterodimerization partner for HER2.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is also the possibility that HER2 heterodimerisation patterns in these cells might be different from those in trastuzumabsensitive BT-474 cells; this in turn might provide differential inputs into Akt regulation in these cell models, a hypothesis supported by Ghosh et al (2011), who demonstrated that HER2 heterodimerisation can be associated with a lower response to trastuzumab. Alternatively, the residual Akt signalling (which is still substantial) observed in MDA-361 cells even after trastuzumab treatment may be enough to maintain cell proliferation, as is the case for PF878 monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have investigated the impact on trastuzumab sensitivity of other ERBB members in breast cancer. For example, trastuzumab reportedly had the greatest benefit for ERBB2-amplified breast cancer driven by ERBB2:ERBB2 homodimers (19). Moreover, ERBB3:ERBB2 dimerization has been reported in many ERBB2-amplified breast cancers (20), leading to investigation of the addition of ERBB3 inhibitors to ERBB2-directed therapy (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%